Metabolic and Cardiovascular Benefits and Risks of EMD386088—A 5-HT6 Receptor Partial Agonist and Dopamine Transporter Inhibitor - Kotańska, Magdalena; Śniecikowska, Joanna; Jastrzębska-Więsek, Magdalena; Kołaczkowski, Marcin; Pytka, Karolina (Frontiers in Neuroscience, 2017)
Since 5-HT6 receptors play role in controlling feeding and satiety and dopamine is essential for normal feeding behavior, we evaluated the ability of EMD 386088 – 5-HT6 receptor partial agonist and dopamine transporter inhibitor – to reduce body weight in obese rats, as well as its anorectic properties (calorie intake reduction) in rat model of excessive eating and the influence on metabolism (plasma glucose and glycerol levels). We also determined the effect of the studied compound on pica behavior in rats and its influence on blood pressure after single administration. EMD 386088 reduced body weight in obese rats fed high-fat diet and decreased calorie intake in both models applied (rat model of obesity and of excessive eating). In both models EMD 386088 regulated plasma glucose and increased plasma glycerol levels. The latter proves that the compound reduced body fat. We think that it might have increased lipolysis, but this requires further studies. The reduction in glucose levels is the first symptom of metabolic disorders compensation. EMD 386088 did not cause pica behavior in rats but increased blood pressure after single administration. We think that partial 5-HT6 agonists might have potential in the treatment of obesity. Thus, EMD 386088 requires extended studies.